Innovating with STEAM in middle school classrooms: remixing education. Issue 3 (8th August 2016) - Herro, Danielle; Quigley, Cassie
Abstract : Purpose: The novelty of science, technology, engineering, art, and mathematics (STEAM) instruction in K-12 classrooms means few cases of STEAM teaching are documented in depth. This paper aims to broaden the conversation regarding STEAM by investigating this new form of education. Design/methodology/approach: As part of a larger multi-year study researching STEAM teaching practices in 14 middle school classrooms in the southeastern United States, the article first summarizes prior research findings and then presents ideas for higher education and K-12 researchers to consider when incorporating STEAM teaching in pre-service education, professional development, and in classrooms. Then, the authors use a second-order narrative approach to describe three cases of teachers enacting STEAM practices in classrooms. Findings: Drawing on the notion of 'remixing' education in the context of STEAM, the authors show how each teacher alters existing practices, instead of offering entirely new instruction, as they implement STEAM teaching. Originality/value: With few cases of STEAM teaching detailed in the depth, this paper advances the understanding of STEAM teaching practices in K-12 classrooms.